Efficient 2,3-Butanediol Production from Cassava Powder by a Crop-Biomass-Utilizer, Enterobacter cloacae subsp. dissolvens SDM - Wang, Ailong (Public Library of Science, 2012)
BACKGROUND: 2,3-Butanediol (BD) is considered as one of the key platform chemicals used in a variety of industrial applications. It is crucial to find an efficient sugar-utilizing strain and feasible carbon source for the economical production of BD. METHODOLOGY/PRINCIPAL FINDINGS: Efficient BD production by a newly isolated Enterobacter cloacae subsp. dissolvens SDM was studied using crop-biomass cassava powder as substrate. The culture conditions and fermentation medium for BD production were optimized. Under the optimal conditions, 78.3 g l(−1) of BD was produced after 24 h in simultaneous saccharification and fermentation (SSF), with a yield of 0.42 g BD g(−1) cassava powder and a specific productivity of 3.3 g l(−1) h(−1). A higher BD concentration (93.9 g l(−1)) was produced after 47 h in fed-batch SSF. CONCLUSIONS/SIGNIFICANCE: The results suggest that strain SDM is a good candidate for the BD production, and cassava powder could be used as an alternative substrate for the efficient production of BD.